SEMINAR PENGABDIAN KEPADA MASYARAKAT PENERAPAN TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA MASYARAKAT DESA TANJUNGWANGI, CICALENGKA, KABUPATEN BANDUNG - Rafika Ratik Srimurni, Rafika Ratik Srimurni; Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Abdussalam, Abdussalam; Jiehad Akbar Pria Utama, Jiehad Akbar Pria Utama; Efni Yusnita, Efni Yusnita; Reina Marsela , Reina Marsela (Media Nusantara, 2024)
The aims and objectives of the community service activities carried out are to introduce and implement a digital technology-based system for Tanjung Wangi village officials and RW officials in the Tanjung Wangi environment Community service is the implementation of the practice of science, technology and arts and culture directly in the community institutionally through scientific methodology as the dissemination of the Tri Dharma of Higher Education as well as noble responsibilities in efforts to develop the capabilities of the community The objectives to be achieved through community service activities are as follows: Increasing the speed of the process of increasing human resource capabilities in line with the rate of development growth.